Foldable Front Child-Seat Design for Scooter Motorcycle: Strength Analysis Under Static and Dynamic Loading - Zulaikah, Siti; Rahmanda, Wahyu; Triawan, Farid (http://dx.doi.org/10.31427/IJSTT.2020.3.2.1, 2020)
Nowadays, motorcycle is considered as one of the most practical transportation mode in Indonesia. It has become a common practice that a motorcycle rider often brings a small child using a child seat while riding. However, the used child seat is usually not safe and can easily fall off from the motorcycle due to the lack of safety consideration. Moreover, it is very risky to ride a motorcycle with a small child, knowing that motorcycles are the highest contributor to road traffic accidents. For this reason, this paper proposes a primary design idea of a foldable child safety-seat that can be placed on the front part of a scooter motorcycle. This design is also completed with strength analysis to evaluate the components’ safety for children under five years old with a weight of around 50 kg. The strength calculation of the frame is done by a theoretical approach under static and dynamic loading. According to the analysis, the proposed child seat design could provide a factor of safety of more than 3.6 for static loading and 1.6 for dynamic loading. This study is expected to be used as a reference for developing a more reliable child safety- seat for motorcycle rider in Indonesia.